Non-fluorine binder, positive plate, lithium ion battery and preparation method of lithium ion battery

By mixing non-fluorine PAN-type binder with hydrogenated nitrile rubber HNBR to form a mixed polymer, the problem of fragility of the positive electrode sheet caused by the high glass transition temperature of the existing non-fluorine positive electrode binder is solved, and the flexibility of the positive electrode sheet is improved and the EU environmental protection requirements are met.

CN119570407APending Publication Date: 2025-03-07TIANJIN JUYUAN NEW ENERGY TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411663374.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07

Smart Images

  • Figure CN119570407A_ABST
    Figure CN119570407A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium battery binders, and particularly relates to a non-fluorine binder, in particular to a non-fluorine binder, a positive plate, a lithium ion battery and a preparation method of the lithium ion battery. Specifically, the adhesive composition comprises a non-fluorine adhesive (PAN type) and hydrogenated nitrile butadiene rubber HNBR. The dry weight mass ratio of the non-fluorine binding agent (PAN type) to the hydrogenated nitrile rubber HNBR is 9: 1. The invention also discloses a positive plate and a lithium ion battery which are prepared by using the binding agent. According to the invention, multi-component modified polyacrylonitrile (PAN type) C25 is mixed with 10% hydrogenated nitrile butadiene rubber HNBR, and a mixed polymer is formed in a solution blending manner, so that the purpose of reducing the glass transition temperature is achieved. The flexibility of the positive plate prepared by using the binder is improved, and the requirements of battery cell processing are also met. As the binder does not contain fluorine element, the lithium ion battery prepared from the binder also meets the environmental protection requirements of European Union.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery binders, and in particular relates to a non-fluorine binder, and specifically relates to a non-fluorine binder, a positive electrode sheet, a lithium ion battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have high energy density and long cycle life, and are widely used in portable electronic devices, automobiles, energy storage and other fields. The preparation method of the positive and negative electrodes of lithium-ion batteries is to mix the positive electrode active material or the negative electrode active material with the electrode binder, conductive agent, etc. into a slurry, apply it to the corresponding current collector, and obtain it through drying, rolling, slitting and other processing techniques. At present, the main binder for the positive electrode of lithium-ion batteries is PVDF, which has the outstanding characteristics of strong antioxidant ability, good thermal stability and easy dispersion.

[0003] In the future, a bill proposed by the European Union will restrict the use of PVDF in the production of positive electrode plates. Therefore, the use of non-fluorine positive electrode binders to replace PVDF is imperative. At present, the main PAN type is used in the industry to replace PVDF binders. Although the electrical performance is comparable to that of batteries using PVDF binders, its high glass transition temperature causes the positive electrode plates to be brittle and the winding to lose powder, which cannot meet the battery manufacturing process, so it cannot be simply replaced. The binder used in patent publication number: CN115939399A is a blended polymer formed by blending a non-fluorine binder with a PVDF binder through a solution, thereby achieving the purpose of lowering the glass transition temperature and improving the flexibility of the electrode. However, due to the still existing use of PVDF, the problem cannot be fundamentally solved. Summary of the invention

[0004] The present invention aims to overcome the shortcomings of the prior art and provide a binder which is a mixture of a non-fluorinated PAN binder and a hydrogenated nitrile rubber HNBR binder, and a positive electrode sheet and a lithium ion battery prepared using the binder.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a non-fluorine adhesive, including: non-fluorine adhesive PAN and hydrogenated nitrile rubber HNBR.

[0006] The dry weight ratio of the non-fluorine binder PAN to the hydrogenated nitrile rubber HNBR is 9:1.

[0007] The residual double bond unsaturation of the hydrogenated nitrile rubber HNBR is ≤0.9%, and the glass transition temperature is between -65°C and -15°C. The hydrogenated nitrile rubber HNBR exists in the form of a solution, and its solid content is 6% to 8%, and the solvent is N-methylpyrrolidone NMP, and the solvent content is 92% to 94%. In addition, the oxidation decomposition voltage of the hydrogenated nitrile rubber HNBR is greater than 5V, and when preparing the lithium-ion battery of this case, the voltage range of the hydrogenated nitrile rubber HNBR is 2.75 to 5V, so that the hydrogenated nitrile rubber HNBR is not oxidatively decomposed.

[0008] The non-fluorine binder PAN type is a group added to the side chain to improve the flexibility and interface bonding strength of the electrode. Preferably, the non-fluorine binder PAN type is multinarily modified polyacrylonitrile (PAN type) C25.

[0009] A positive electrode sheet comprises the non-fluorine binder, a positive electrode conductor, a positive electrode active material and a positive electrode solvent.

[0010] The positive electrode conductive agent is a mixture of carbon black and carbon nanotubes, and the mass ratio of the two is 0.6:(0.4-0.9). The positive electrode active material is lithium cobalt oxide, and the positive electrode solvent is N-methylpyrrolidone NMP.

[0011] A method for preparing a positive electrode sheet comprises the following steps: mixing a non-fluorine binder, a positive electrode conductive agent, a positive electrode active material and a solvent to form a positive electrode slurry, wherein the positive electrode slurry has a viscosity of 6000-7000 mPa·s and a solid content of 70%-75%, uniformly coating the positive electrode slurry on the surface of an aluminum foil current collector, drying, rolling the electrode sheet and shearing the positive electrode sheet.

[0012] A lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator includes but is not limited to at least one of a polyolefin (PO) separator, a polyester film, a cellulose film, a polyimide film (PI), a polyamide film (PA), a spandex or aramid film, a woven film, a non-woven film (non-woven fabric), a microporous film, a composite film, a separator paper, a rolled film or a spun film.

[0013] The electrolyte includes but is not limited to lithium salt and non-aqueous solvent.

[0014] A method for preparing a negative electrode sheet comprises the following steps: mixing artificial graphite, conductive graphite, and conductive carbon black dry powder uniformly, adding dispersant lithium carboxymethyl cellulose and deionized water for dispersion, and finally adding binder styrene-butadiene rubber to prepare a negative electrode slurry. The dry weight mass ratio of artificial graphite, conductive graphite, conductive carbon black, lithium carboxymethyl cellulose, and styrene-butadiene rubber is 96.5:0.5:0.5:1:1.5, the viscosity of the negative electrode slurry is 2000-2400 mPa·s, the solid content is 45%-50%, and the negative electrode slurry is uniformly coated on the surface of the copper foil current collector, and after drying, rolling and shearing are performed to obtain a negative electrode sheet.

[0015] A method for preparing a lithium ion battery comprises the following steps: preparing the above-mentioned positive electrode sheet, negative electrode sheet and separator into an electrode group by winding, and preparing a soft-pack polymer lithium ion battery after liquid injection, formation, capacity division and aging.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present application utilizes the compatibility characteristics of mixed polymers, that is, if the two polymer components are compatible and the blend is a homogeneous system, there is only one glass transition temperature, and this glass transition temperature Tg is between the glass transition temperatures Tg of the two mixed polymers and satisfies the FOX formula: Therefore, the non-fluorine binder of the present application adopts multi-modified polyacrylonitrile (PAN type) C25 mixed with 10% hydrogenated nitrile rubber HNBR, and forms a mixed polymer by solution blending, so as to achieve the purpose of lowering the glass transition temperature. The positive electrode sheet prepared using the binder has improved flexibility and meets the requirements of battery cell processing. Since the binder does not contain fluorine, the lithium-ion battery made from it also meets the EU environmental protection requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a picture of the flexibility test of the positive electrode sheet after rolling and die cutting in Example 1 of the present invention on a cylindrical bending tester using a 2mm curling needle (the binder is a non-fluorine binder 90% multinarily modified polyacrylonitrile (PAN type) C25 mixed with 10% hydrogenated nitrile rubber HNBR).

[0019] Figure 2 This is a picture of the flexibility test of the positive electrode sheet after rolling and die cutting in Comparative Example 1 of the present invention using a 2mm curling needle on a cylindrical bending tester (the binder is a pure non-fluorine binder multinarily modified polyacrylonitrile (PAN type) C25).

[0020] Figure 3 The 25°C cycle performance curves of Example 1 and Comparative Example 1 of the present invention are shown.

[0021] Figure 4 45°C cycle performance curves of Example 1 and Comparative Example 1 of the present invention.

[0022] Figure 5 1 is the rate discharge performance curve of Example 1 and Comparative Example 1 of the present invention.

[0023] Figure 6 The high and low temperature discharge performance curves of Example 1 and Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0025] Embodiment 1:

[0026] A method for preparing a lithium ion battery comprises the following steps:

[0027] 1) Preparation of positive electrode sheet: Mix the carbon nanotube conductive paste with the binder to make a conductive glue, then add conductive carbon black to the glue, and make the positive electrode active material lithium cobalt oxide into a positive electrode paste. The dry weight ratio of lithium cobalt oxide, conductive carbon black, carbon nanotube conductive agent and binder is 98:0.6:0.4:1, the viscosity of the positive electrode paste is 6200mPa·s, the solid content is 75%, and it is evenly coated on the surface of the 10μm thick aluminum foil current collector with a surface density of 35.5m2 / g, followed by rolling, compaction density of 4.1g / cc, and then die-cutting to obtain a positive electrode sheet. Among them, the binder is made by mixing the non-fluorine binder polyacrylonitrile (PAN type) C25 and hydrogenated nitrile rubber HNBR at a dry weight ratio of 9:1.

[0028] 2) Preparation of negative electrode sheet: After artificial graphite, conductive graphite, and conductive carbon black dry powder are mixed evenly, dispersant lithium carboxymethyl cellulose and deionized water are added for dispersion, and finally binder styrene-butadiene rubber is added to prepare negative electrode slurry. The dry weight mass ratio of artificial graphite, conductive graphite, conductive carbon black, lithium carboxymethyl cellulose, and styrene-butadiene rubber is 96.5:0.5:0.5:1:1.5, the negative electrode slurry has a viscosity of 2400mPa·s and a solid content of 45%. It is evenly coated on the surface of a 6μm thick copper foil current collector with a surface density of 19.6m2 / g. After drying, it is rolled and sheared to obtain a negative electrode sheet.

[0029] 3) The separator includes but is not limited to polyethylene (PE), polypropylene (PP), polytetrafluoroethylene-based polyolefin (PO) separators, polyester films (such as polyethylene terephthalate (PET) films), cellulose films, polyimide films (PI), polyamide films (PA), spandex or aramid films, woven films, nonwoven films (nonwoven fabrics), microporous films, composite films, separator paper, rolled films or spun films, etc. There is no particular limitation on the separator in this application, as long as the purpose of this application can be achieved.

[0030] 4) The electrolyte may include, but is not limited to, a lithium salt and a non-aqueous solvent. In the embodiment of the present application, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB or lithium difluoroborate. Preferably, the lithium salt includes LiPF6. The non-aqueous solvent may include, but is not limited to, at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents.

[0031] 5) Preparation of lithium-ion battery: The positive electrode sheet, negative electrode sheet and separator are wound into an electrode group, which is packaged with an aluminum-plastic film with a thickness of 113 μm. After liquid injection, formation, capacity division and aging, a soft-pack polymer lithium-ion battery with a capacity of 3.5 Ah is prepared.

[0032] Comparative Example 1:

[0033] The difference between the comparative example and the embodiment is that the binder added in the preparation of the positive electrode plate in step 1) is a pure non-fluorine binder multinarily modified polyacrylonitrile (PAN type) C25.

[0034] A lithium-ion battery performance testing method:

[0035] 1) Capacity, energy density, and first efficiency test: At 25°C, the battery is charged to 4.5V at a constant current of 0.2C, then charged to a cutoff current of 0.05C at a constant voltage, and discharged to 3V at a constant current of 0.2C.

[0036] 2) 25℃ cycle performance: At 25℃, the battery is charged at a constant current of 0.8C to 4.5V, then charged at a constant voltage to a cutoff current of 0.05C, and discharged at a constant current of 0.5C to 3V.

[0037] 3) 45℃ cycle performance: At 45℃, the battery is charged to 4.5V at a constant current of 0.8C, then charged to a cutoff current of 0.05C at a constant voltage, and discharged to 3V at a constant current of 0.5C.

[0038] 4) Rate discharge performance: At 25°C, the battery is charged to 4.5V at a constant current of 0.5C, then charged to a cut-off current of 0.05C at a constant voltage, and discharged to 3V at rates of 0.2C / 0.5C / 1.0C / 1.5C / 2C respectively. The capacity retention rate at each rate is calculated based on the capacity at the 0.2C discharge rate.

[0039] 5) High and low temperature discharge test: The battery is charged to 4.5V at 0.5C constant current, then charged to a cut-off current of 0.05C at constant voltage, and discharged to 3V at 0.2C constant current at 25 / 60 / 45 / 0 / -10 / -20℃ respectively. The capacity retention rate at each temperature is calculated based on the discharge capacity at 25℃. As shown in Table 1:

[0040] Test items Example 1 Comparative Example 1 Capacity(Ah) 3.425 3.427 Energy density (Wh / L) 752 753 Cell internal resistance (mΩ) 30.2 28.8 First charge and discharge efficiency (%) 89.90% 90.10% Capacity retention rate after 1000 cycles at 25°C (%) 72.70% 72.20% Capacity retention rate after 600 cycles at 45°C (%) 85.80% 85.40% 25 degrees cycle 1000 times battery internal resistance (mΩ) 43.1 41.9 45 degrees cycle 600 times battery internal resistance (mΩ) 47.2 45.5

[0041] Table 1

[0042] Table 1 summarizes the relevant performance data of the batteries of the embodiments and comparative examples. Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 The performance curves of the state of the electrode after folding after rolling, 25°C cycle, 45°C cycle, rate discharge and high and low temperature discharge are shown respectively.

[0043] from Figure 1 It can be seen that when 4.1g / cc of the compacting binder is a non-fluorine binder multi-modified polyacrylonitrile (PAN type) C25 mixed with 10% hydrogenated nitrile rubber HNBR, the pole piece is folded in half after rolling without bifurcation, falling off, light leakage, etc., and the pole piece has good flexibility.

[0044] from Figure 2 It can be seen that when the compaction binder of 4.1g / cc is pure non-fluorine binder multinarily modified polyacrylonitrile (PAN type) C25, the electrode piece is folded in half after rolling and breaks and falls off, and the electrode piece is brittle.

[0045] It can be concluded that compared with the use of pure non-fluorine binder multinarily modified polyacrylonitrile (PAN type) C25 in the comparative example, the lithium-ion battery prepared by using a binder composed of non-fluorine binder multinarily modified polyacrylonitrile (PAN type) C25 and hydrogenated nitrile rubber HNBR in a dry weight ratio of 9:1 has no obvious differences in capacity, energy density, initial charge and discharge efficiency, internal resistance, cycle, rate and high and low temperature discharge, indicating that the electrical performance of the battery produced is not affected.

[0046] Therefore, the non-fluorine binder of the present application adopts multi-modified polyacrylonitrile (PAN) C25 mixed with 10% hydrogenated nitrile rubber HNBR, and forms a mixed polymer by solution blending, so as to achieve the purpose of lowering the glass transition temperature. The positive electrode sheet prepared using the binder has improved flexibility and meets the requirements of battery cell manufacturing process.

[0047] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A non-fluorine binder, characterized in that: include: Non-fluorinated binders PAN and hydrogenated nitrile rubber HNBR.

2. The non-fluorine binder according to claim 1, characterized in that: The dry weight ratio of the non-fluorine binder PAN to the hydrogenated nitrile rubber HNBR is 9:

1.

3. The non-fluorine binder according to claim 1, characterized in that: The residual double bond unsaturation of the hydrogenated nitrile rubber HNBR is ≤0.9%, and the glass transition temperature is between -65°C and -15°C. The hydrogenated nitrile rubber HNBR exists in the form of a solution, the solid content of the hydrogenated nitrile rubber HNBR in the solution is 6% to 8%, and the solvent is N-methylpyrrolidone NMP, and the solvent content is 92% to 94%.

4. The non-fluorine adhesive according to claim 1, characterized in that: The non-fluorine binder PAN type is a group added to the side chain to improve the flexibility and interface bonding strength of the electrode. Preferably, the non-fluorine binder PAN type is multinarily modified polyacrylonitrile (PAN type) C25.

5. A positive electrode sheet, characterized in that: The invention comprises the non-fluorine binder according to any one of claims 1 to 4, a positive electrode conductor, a positive electrode active material and a positive electrode solvent.

6. The positive electrode sheet according to claim 5, characterized in that: The positive electrode conductive agent is a mixture of carbon black and carbon nanotubes, and the mass ratio of the two is 0.6:(0.4-0.9). The positive electrode active material is lithium cobalt oxide, and the positive electrode solvent is N-methylpyrrolidone NMP.

7. A method for preparing a positive electrode sheet according to any one of claims 5 to 6, characterized in that: The method comprises the following steps: mixing a non-fluorine binder, a positive electrode conductive agent, a positive electrode active material and a solvent to form a positive electrode slurry, wherein the positive electrode slurry has a viscosity of 6000-7000 mPa·s and a solid content of 70%-75%, uniformly coating the positive electrode slurry on the surface of an aluminum foil current collector, and rolling the electrode sheet after drying, and shearing the positive electrode sheet.

8. A lithium ion battery, characterized in that: The invention comprises the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte according to any one of claims 8, The separator includes but is not limited to at least one of polyolefin (PO) separators, polyester membranes, cellulose membranes, polyimide membranes (PI), polyamide membranes (PA), spandex or aramid membranes, woven membranes, nonwoven membranes (nonwoven fabrics), microporous membranes, composite membranes, separator paper, rolled membranes or spun membranes, etc.; The electrolyte includes but is not limited to lithium salt and non-aqueous solvent.

9. The lithium-ion battery according to claim 8, characterized in that: The negative electrode sheet preparation method comprises the following steps: after artificial graphite, conductive graphite and conductive carbon black dry powder are mixed evenly, dispersant lithium carboxymethyl cellulose and deionized water are added for dispersion, and finally a binder styrene-butadiene rubber is added to prepare a negative electrode slurry. The dry weight mass ratio of artificial graphite, conductive graphite, conductive carbon black, lithium carboxymethyl cellulose and styrene-butadiene rubber is 96.5:0.5:0.5:1:1.5, the viscosity of the negative electrode slurry is 2000-2400 mPa·s, the solid content is 45%-50%, and the negative electrode slurry is evenly coated on the surface of the copper foil current collector, and after drying, the negative electrode sheet is obtained by rolling and shearing.

10. A method for preparing a lithium ion battery according to claim 8 or 9, characterized in that: The method comprises the following steps: preparing the positive electrode sheet, the negative electrode sheet and the separator into an electrode group by winding, and preparing a soft-package polymer lithium-ion battery after liquid injection, formation, capacity division and aging.

Citation Information

Patent Citations

  • Use method of non-fluorine binder

    CN115939399A